Non-Custodial Sanctions under Indonesia's Criminal Code Reform: A Comparative Analysis through the Lens of Islamic Legal Theory - Ria Anggraeni Utami; Herlambang; Antory Royan Adyan (YURIS: Journal of Court and Justice, 2026)
This study explores the integration of non-custodial sanctions under Indonesia's new Criminal Code (Law No. 1/2023). It addresses the issue of prison overcrowding by analyzing these alternative sanctions from a modern and Islamic legal perspectiv. The objective of this study is to understand the effectiveness of non-custodial sanctions and the contribution of Islamic principles in developing a more humane and just penal system This research applies a normative juridical method utilizing statutory, conceptual, and comparative approaches. Data analysis is conducted through a qualitative analysis of primary and secondary legal sources using a prescriptive-analytical approach. The findings indicate that non-custodial sanctions are highly relevant to Islamic legal theory, particularly within the framework of ta’zir, which is flexible and educative in nature. The principles of justice (al-‘adl), public welfare (al-maslahah), and prevention (al-zajr) in Islamic law support the application of alternative punishments such as community service, fines, and rehabilitation in order to achieve social restoration. In conclusion, the strengthening of non-custodial sanctions aligns with the concept of maqashid al-shari’ah and offers a more humane and effective solution in achieving the objectives of modern sentencing.